Lampu PJU Otomatis - sutono sutono; Mochamad Fajar Wicaksono (Computer Engineering Departement, Universitas Komputer Indonesia, 2018)
The purpose of this study is to assist the Government in overcoming the energy crisis, especially the problem of Public Road Lighting. In big cities it is very dominant to find a PJU lamp which is indeed a vital public facility, especially at night. The more placement points of PJU lights will certainly have an energy crisis, although there is a way to replace LED lights as a solution to overcome the energy crisis. on this basis the Researcher designed a PJU lamp with a solar cell power source to reduce the burden of the PLN which was already large enough to meet the electricity needs in big cities such as Jakarta, Bandung, Surabaya and other cities in Indonesia. So that these goals can be fulfilled, then the design of this tool uses a multi sensor so that the PJU lights turn on at night and there are objects around the PJU lights.